Kepemimpinan dalam Islam: Analisis Konsep "Al-Tawazun" dalam Al-Qur’an - Abdurrohim; Ely Fitriani (TADARUS, 2025)
Leaders and leadership are two interrelated aspects that play a crucial role in the life of a society, a nation, and a state. Islam, as a religion of rahmatan lil-‘alamin, also places leadership and the position of a leader as fundamental components of its teachings. The purpose of this study is to analyze the concept of leadership in Islam through the lens of the al-Tawazun principle as reflected in Qur’anic verses, specifically Surah Ar-Rahman verses 1–9. This research employs a qualitative method using a library-based approach, focusing on scholarly literature derived from books and peer-reviewed journal articles. The findings indicate that the concept of al-Tawazun is highly relevant to the Islamic concept of leadership (khalifah). The notion of balance articulated in these Qur’anic verses serves as evidence of the majesty and grandeur of Allah SWT. As leaders, human beings bear the responsibility to maintain balance and harmony within the universe, both in their relationship with the natural environment and in their interactions with fellow human beings.